Joint attention difficulties in autistic adults: An interactive eye-tracking study. (May 2018) - Caruana, Nathan; Stieglitz Ham, Heidi; Brock, Jon; Woolgar, Alexandra; Kloth, Nadine; Palermo, Romina; McArthur, Genevieve
Joint attention – the ability to coordinate attention with a social partner – is critical for social communication, learning and the regulation of interpersonal relationships. Infants and young children with autism demonstrate impairments in both initiating and responding to joint attention bids in naturalistic settings. However, little is known about joint attention abilities in adults with autism. Here, we tested 17 autistic adults and 17 age- and nonverbal intelligence quotient–matched controls using an interactive eye-tracking paradigm in which participants initiated and responded to joint attention bids with an on-screen avatar. Compared to control participants, autistic adults completed fewer trials successfully. They were also slower to respond to joint attention bids in the first block of testing but performed as well as controls in the second block. There were no group differences in responding to spatial cues on a non-social task with similar attention and oculomotor demands. These experimental results were mirrored in the subjective reports given by participants, with some commenting that they initially found it challenging to communicate using eye gaze, but were able to develop strategies that allowed them to achieve joint attention. Our study indicates that for many autistic individuals, subtle difficulties using eye-gaze information persist well into adulthood.